Analisis Dinamika Pola Mobilitas Tenaga Kerja di Indonesia: Studi Kasus Tren #KABURAJADULU - Chiky Cinta Aprillia; Novita Mayasari; Dafa Aurella; Mujiatin Eka Lestari; Jidan Jabbar Arfat; Hernanda Wachid Prasetyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study examines the shifting patterns of labor mobility in Indonesia influenced by the social media trend #KaburAjaDulu2025. This phenomenon has seen an increase in the number of Indonesian workers seeking better jobs abroad in response to the stagnation of the domestic job market. This research discusses the various components that drive such mobility, as well as how it impacts the economic and social life of the community. The research was conducted using a descriptive qualitative approach and a literature study. The results of the study show that economic inequality, low wages, technological advances, and easy access to the internet around the world are factors that drive the movement of Indonesian workers. Permanent migration, shuttle mobility and circular migration are the three main mobility patterns that emerge. This mobility can improve family health, increase knowledge, and improve the economy of the region of origin. However, this labor mobility also triggers a number of challenges, such as the loss of quality labor (brain drain), development inequality between regions, and the potential for increased unemployment and social problems in the destination area. Therefore, more responsive and adaptive policies, increased investment in productive sectors, and stronger protection for migrant workers are needed, so that this phenomenon can be utilized as an opportunity to improve the livelihood of migrant workers.